2022
DOI: 10.1002/hfm.20959
|View full text |Cite
|
Sign up to set email alerts
|

Hand anthropometric dimensions and strengths in workers: A comparison of three occupations

Abstract: The purpose of this study was to measure and compare the hand anthropometric dimensions and strengths of three different occupations. A cross-sectional study was designed to measure 34 hand dimensions and 4 hand strengths of 558 participants consisted of office workers, vehicle mechanics, and farmers. A digital caliper, a hand dynamometer, and a pinch meter were used to collect data. Percentile values for each measurement were tabulated at the 5th, 50th, and 95th percentile levels. The analysis of variance, t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The results of the mentioned study substantiate the results of our study, in which significant statistical differences were identified between different anthropometric parameters between the right hand (dominant, in the case of the present study) and the left hand. Numerous studies have highlighted anthropometric differences between the right-hand and the lefthand parameters, depending on gender [61][62][63]; ethnicity [64,65]; occupation [66,67]; and laterality [68][69][70]. A study conducted on 161 university student subjects identified significant differences between the male and female samples, with the male group recording an average hand width of 7.57 cm [71].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the mentioned study substantiate the results of our study, in which significant statistical differences were identified between different anthropometric parameters between the right hand (dominant, in the case of the present study) and the left hand. Numerous studies have highlighted anthropometric differences between the right-hand and the lefthand parameters, depending on gender [61][62][63]; ethnicity [64,65]; occupation [66,67]; and laterality [68][69][70]. A study conducted on 161 university student subjects identified significant differences between the male and female samples, with the male group recording an average hand width of 7.57 cm [71].…”
Section: Discussionmentioning
confidence: 99%